Peterson's 440 colleges for top students (Thomson Peterson's, 2007)
The college guide for high-achieving students. Top students will find an enticing collection of prospective colleges in this annually updated guide, including all the relevant details on academics, student body, facilities, campus life, and more. It's perfect for the motivated student seeking a challenging and fulfilling collegiate experience.